THE POLITENESS CHARACTERISTICS OF ELEMENTARY SCHOOL STUDENTS WITH MIGRANT PARENTS: A CRITICAL ANALYSIS - Agus Setyabudi; Ana Andriani; Y. Suyitno; Wakhudin (SOSIOEDUKASI, 2025)
Students who grow up without direct parental guidance often experience changes in their social and emotional behavior. This study analyzes how polite character is formed in elementary school students in the Punggelan cluster whose parents have migrated. The research method was qualitative with a case study design. The subjects were students, teachers, and substitute guardians or family members living with the students. Data were collected through observation, interviews, and documentation, then analyzed through data condensation, data presentation, and conclusion drawing. Data validity was verified using source and method triangulation techniques. The results showed that the polite character of elementary school students whose parents have migrated showed behavioral variations across all indicators of politeness. Students who received regular communication and emotional guidance from their parents were able to apply politeness more consistently, such as respecting the rights of others, using polite language, demonstrating non-verbal politeness, and respecting teachers and peers. In contrast, students who were cared for by substitute guardians tended to exhibit less consistent behavior, such as interrupting, difficulty maintaining attention, using impolite language, avoiding eye contact, or joking excessively. This variation is influenced by parental presence, parenting styles, teacher training and guidance at school, and the influence of the social environment. Research confirms that the development of good manners in children from migrant families is a result of interactions between family, school, and the environment. Therefore, consistent training and support across contexts are key to fostering stable polite behavior.